2016
DOI: 10.1080/21688370.2016.1268667
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic interactions ofPlasmodiumspp. with vascular endothelium

Abstract: Plasmodial species are protozoan parasites that infect erythrocytes. As such, they are in close contact with microvascular endothelium for most of the life cycle in the mammalian host. The hostparasite interactions of this stage of the infection are responsible for the clinical manifestations of the disease that range from a mild febrile illness to severe and frequently fatal syndromes such as cerebral malaria and multi-organ failure. Plasmodium falciparum, the causative agent of the most severe form of malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 162 publications
1
22
0
Order By: Relevance
“…PfEMP1-receptor interactions have been shown to activate signalling pathways in endothelial cells (Wu et al, 2011;Gillrie & Ho, 2017), but the effect of these events on pathology is unclear. More recent work has also suggested that as well as cytoadherencemediated events, the accumulation of sequestered IE in vessels may facilitate endothelial dysfunction caused by the local release of soluble mediators following schizont rupture (Gallego-Delgado & Rodriguez, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…PfEMP1-receptor interactions have been shown to activate signalling pathways in endothelial cells (Wu et al, 2011;Gillrie & Ho, 2017), but the effect of these events on pathology is unclear. More recent work has also suggested that as well as cytoadherencemediated events, the accumulation of sequestered IE in vessels may facilitate endothelial dysfunction caused by the local release of soluble mediators following schizont rupture (Gallego-Delgado & Rodriguez, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the release of intracellular erythrocytic contents triggers endothelial dysfunction. In fact, specific components of the infected erythrocyte have been proposed to contribute to the P. falciparum -induced endothelial disruption, including parasite histones, histidine rich protein II and heme [11]. …”
mentioning
confidence: 99%
“…It has been shown that P. falciparum antigens are present on the surface of infected erythrocytes and bind to the receptors expressed on the VE [72] . After invasion, Plasmodium modulates endothelial function either by direct adhesion to the EC receptors or by releasing parasite products that can induce EC activation, leading to the disruption of the EC barrier [73] . It has also been shown that histones released from merozoites (HeH) stimulate the production of inflammatory mediators by primary human dermal microvascular endothelial cells, supporting the pathogenic role of both host-and pathogen-derived histones in P. falciparum caused malaria [128] .…”
Section: Role Of the Ve In Malariamentioning
confidence: 99%